Critical choices for China's agricultural policy - Fan, Shenggen; Cohen, Marc J. (International Food Policy Research Institute, 1999)
Economic reforms initiated in 1978 brought rapid economic growth in China. Fundamental changes occurred in the national economic system. While the reforms were focused on agriculture, as expected, the role of the agricultural sector declined, and the manufacturing and service sectors grew much faster than the rest of the economy. Land, labor, and water shifted to nonagricultural uses. And farmers' incentives for agricultural production deteriorated.